2020
DOI: 10.1002/esp.4776
|View full text |Cite
|
Sign up to set email alerts
|

Morphodynamics of alternate bars in the presence of riparian vegetation

Abstract: Alpine gravel‐bed rivers are dynamic systems that have been subjected to many anthropic alterations in the past centuries. Riparian vegetation development on previously bare sediment bedforms has been a common adjustment, raising important management issues in terms of flood risks and biodiversity. Many of these rivers are also channelized, and as a result present a pattern of alternate bars. Considering recent advances in numerical biomorphodynamic modeling, this study aims at exploring numerically the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 104 publications
(251 reference statements)
11
22
0
Order By: Relevance
“…Such balance can vary following a reduction in frequency and magnitude of floods, but also by biotic factors such as the arrival of invasive species with better survival ability and colonisation strategies than native species 54 . Previous modelling studies on alternate bars have shown the role played by flow variability and vegetation characteristics in modulating the transition between vegetated and bare states 33,34,55 , indicating the presence of two stable alternative states on alternate bars, steady-vegetated bars and migrating bare bars. Our results add on these findings, and provide insights on the role played by both above-and below-ground plant traits and their development, as well on the whole flow regime including low flows and floods with different magnitude, duration, and frequency, which are often not considered.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Such balance can vary following a reduction in frequency and magnitude of floods, but also by biotic factors such as the arrival of invasive species with better survival ability and colonisation strategies than native species 54 . Previous modelling studies on alternate bars have shown the role played by flow variability and vegetation characteristics in modulating the transition between vegetated and bare states 33,34,55 , indicating the presence of two stable alternative states on alternate bars, steady-vegetated bars and migrating bare bars. Our results add on these findings, and provide insights on the role played by both above-and below-ground plant traits and their development, as well on the whole flow regime including low flows and floods with different magnitude, duration, and frequency, which are often not considered.…”
Section: Discussionmentioning
confidence: 92%
“…Despite modelling efforts to include a more detailed description of vegetation-related feedbacks are mounting 32 , 33 , there is still a lack of appropriate models that links environmental factors with plant morphological traits and describes the associated feedbacks. So far, models have mostly treated vegetation as a whole 34 , not distinguishing between above- and below-ground traits, or have focused on spatial and temporal scales that hindered a clear identification of their role 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, in our study area, sediment deposition may not be confined within the separation zone (Best, 1987) and that the enhancement of bar dimensions can be related to the presence of vegetation, which definitely plays an important role in making the bars stable (Calvani, Francalanci, & Solari, 2018;Jourdain, Claude, Tassi, Cordier, & Antoine, 2020), by promoting deposition and thus enhancing their dimensions.…”
Section: River Confluences Morphodynamics In Presence Of Riparian Vegetationmentioning
confidence: 81%
“…Since the end of the 20th century, there has been a relative shortage of coarse particle input, and an excess of fine particles. The resulting imbalance led to erosion of the main channel, aggradation and fixation of gravel bars due to massive fine sediment deposits and riparian vegetation growth (Jourdain et al, 2020).…”
Section: Objectives and Site Descriptionmentioning
confidence: 99%